PENGARUH MODEL KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR IPS SISWA DI SEKOLAH DASAR - Suti Nasution, Mora; Miaz, Yalvema; M.Pd, Rahmatina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research was to effect of kooperatif type Student Teams Achievement Division (STAD) model on student learning outcomes in Social Science Class V at SDN 13 Cingkariang Kabupaten Agam, in the odd semester of the academic year 2018/2019. This research is a quantitative research with experimental type and quasy experimental research design. Sampling data is taken by purposive sampling. The sample of this study amounted to 50 people, with a population of 146 people. Based on the research that has been done, obtained t count> t table, 2.38 > 1,68 with α = 0.05 is means Ho is rejected and Ha accepted, it meaning there is influence the use of Student Teams Achievement Division (STAD) model of student learning outcomes in Social Science Class V SD N 13 Cingkariang Kabupaten Agam.Keywords: Social Studies Learning Outcomes, STAD Model